Combinational Treatment of Bioscaffolds and Extracellular Vesicles in Spinal Cord Injury - Wang, Xizhi; Botchway, Benson O. A.; Zhang, Yong; Yuan, Jiaying; Liu, Xuehong (Frontiers in Molecular Neuroscience, 2019)
Spinal cord injury (SCI) can result in an irreversible disability due to loss of sensorimotor function below the lesion. Presently, clinical treatments for SCI mainly include surgery, drugs and postoperative rehabilitation. The prospective roles of bioscaffolds and exosomes in several neurological diseases have been reported. Bioscaffolds can reconnect lesion gaps as well as transport cells and bioactive factors, which in turn can improve axonal and functional regeneration. Herein, we explicate the respective roles of bioscaffolds and exosomes in SCI, and elucidate on the usage of combinational therapy involving bioscaffolds and exosomes in improving SCI.